Taking Construction Grammar One Step Further: Families, Clusters, and Networks of Evaluative Constructions in Russian - Endresen, Anna; Janda, Laura A. (Frontiers in Psychology, 2020)
We present a case study of grammatical constructions and how their function in a single language (Russian) can be captured through semantic and syntactic classification. Since 2016 an on-going joint project of UiT The Arctic University of Norway and the National Research University Higher School of Economics in Moscow has been collecting and analyzing multiword grammatical constructions of Russian. The main product is the Russian Constructicon (https://site.uit.no/russian-constructicon/), which with over two thousand two hundred constructions (and more being continuously added), is arguably the largest openly available constructicon resource for any language. The combination of this large size with depth of analysis, containing both syntactic and semantic tags, makes it possible to view the interrelation of constructions as families and discover trends in their behavior. Our annotation includes fifty-three semantic tags of varying frequency, with three tags that are by far more frequent than all the rest, accounting for 30% of the entire inventory of the Russian Constructicon. These three semantic types are Assessment, Attitude, and Intensity, all of which convey a speaker’s evaluation of a topic, in contrast to most of the other tags (such as Time, Manner, and Comparison). Assessment and Attitude constructions are investigated in greater detail in this article. Secondary semantic tags reveal that negative evaluation among these most common semantic types is more than twice as frequent as positive evaluation. Examples of negative evaluations for these three types are: for Assesment NP-Nom (byt’) tak sebe, as in kartina tak sebe ‘the painting is so-so [lit. thus self]’; for Attitude s Pron-Gen xvatit, as in s menja xvatit ‘I’m fed up [lit. from me enough]’; for Intensity užasno XP, as in užasno skučno ‘extremely [lit. terribly] boring’. Our semantic and syntactic classification of this large body of Russian constructions makes it possible to postulate patterns of grammatical constructions constituting a radial category with central and peripheral types. Classification of large numbers of constructions reveals systematic relations that structure the grammar of a language.